2022
DOI: 10.1140/epjc/s10052-022-10474-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of cosmic space and horizon entropy maximization from Tsallis and Cirto entropy

Abstract: In this note by use of the idea of the emergence of cosmic space suggested by Padmanabhan (Emergence and expansion of cosmic space as due to the quest for holographic equipartition; Res Astro Astrophys 12:891, 2012), we derive the modified Friedmann equation of a Friedmann-Robertson-Walker (FRW) Universe from Tsallis and Cirto entropy in $$(n+1)$$ ( n + 1 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 107 publications
5
5
0
Order By: Relevance
“…As a result, we have shown that both arguments lead to the same constraint, thus allowing to interpret the law of emergence as a tendency of our Universe to extremize horizon entropy. It is worth mentioning that this outcome fits with results formerly obtained in Einstein, Gauss-Bonnet and Lovelock gravities [25,26] and in the context of non-extensive Tsallis entropy [21]. In this sense, our work provides an effort toward the extension of the gravity-thermodynamic connection to a quantum gravity-like scenario.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As a result, we have shown that both arguments lead to the same constraint, thus allowing to interpret the law of emergence as a tendency of our Universe to extremize horizon entropy. It is worth mentioning that this outcome fits with results formerly obtained in Einstein, Gauss-Bonnet and Lovelock gravities [25,26] and in the context of non-extensive Tsallis entropy [21]. In this sense, our work provides an effort toward the extension of the gravity-thermodynamic connection to a quantum gravity-like scenario.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly to [21], the definition (13) of number of surface degrees of freedom becomes 3 and ( 23) are correctly dimensionless for any value of n and . On the other hand, it is not clear how the corresponding definitions in [21] can be such for Tsallis pa-…”
Section: Modified Friedmann Equation From the Law Of Emergence In (N ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the author obtained the Friedmann equations from a newly proposed modified law of emergence. Later, this was extended to (n + 1)-dimensional non-flat FRW universe by Chen [61]. Recently, Basari et al [49] obtained the law of emergence through a unified expansion law derived from the equilibrium first law of thermodynamics, for the Tsallis entropy given by…”
Section: S I Ii a S I S Iimentioning
confidence: 99%